Comparative Efficacy of Low-Dose Alteplase versus Standard Dose among Acute Ischemic Stroke Patients: A Single-Centre Experience in Pakistan: Low-Dose Alteplase versus Standard Dose among Acute Ischemic Stroke Patients - Khan, Tariq; Liaqat, Jahanzeb; Hashmat, Asif; Khan, Ijaz; Khan, Tahir; Rahman, Hameed Ur (Pakistan Journal of Health Sciences, 2026)
Intravenous (IV) alteplase(tPA) at a dose of 0.9 mg /kg is the standard treatment of acute ischemic stroke (AIS), but it carries the risk of intracranial hemorrhage. Objectives: To assess the efficacy and safety of tPA low dose (LD; 0.6 mg/kg) as compared to standard-dose (SD; 0.9 mg/kg) in AIS patients in normal clinical practice. Methods: In this retrospective comparative cohort study, 320 AIS patients administered IV-tPA within 4.5 hours of stroke symptoms were selected in 2 groups (160 patients receiving LD; 0.6mg/kg), and 160 patients (SD; 0.9mg/kg) were developed in the Department of Neurology, Pak Emirates Military Hospital, Rawalpindi, between January 2023 and December 2024. The measured outcomes were functional independence (mRS=02) at 90-day, incidence of symptomatic intracranial hemorrhage (sICH), and 90-day mortality. Results: Few individuals (32.5%) in the (LD; 0.6 mg/kg) group had positive functional outcomes compared to those in the (SD; 0.9 mg/kg) group (40.0%), but the difference was not significant (p=0.152). The (LD; 0.6mg/kg) (1.9% vs. 5.6%) (p=0.038) significantly reduced the risk of sICH. There were no differences in the 90-day mortality rates between the groups (11.3% vs. 13.8%, p=0.299). Adjusted (LD; 0.6 mg/kg) was, however, associated with reduced risk of sICH (aOR 0.30; 95% CI 0.08-0.98; p=0.040) but not functional outcome (aOR 0.82; 95% CI 0.54-1.25; p=0.361). Functional outcomes were strongly predicted by age, baseline NIHSS, and treatment length. Conclusions: In routine clinical practice, (LD; 0.6 mg/kg) was selectively used in higher-risk patients and showed a promising safety profile with functional outcomes broadly comparable to (SD; 0.9 mg/kg) therapy.